The return of inflation - Fred L. Block (economic sociology. perspectives and conversations, 2022)
Back in 1978, when economic sociology was still in an embryonic state, the British sociologist John Goldthorpe published an important paper, "The Current Inflation: Towards a Sociological Account" (Goldthorpe 1978). Goldthorpe rejected the conventional arguments that inflation was the consequence of too much money chasing too few goods or that it could be attributed to excessive public sector spending. He argued instead that inflation was often the result of distributional conflict, particularly between workers and their employers.
Keywords: 300